Impact of the assembly-activating protein on molecular evolution of synthetic adeno-associated virus capsids - Herrmann, Anne-Kathrin; Große, Stefanie; Börner, Kathleen; Krämer, Chiara; Wiedtke, Ellen; Gunkel, Manuel; Grimm, Dirk (Human gene therapy, 2019)
Over the last decade, the role of the assembly-activating protein (AAP) has begun to be dissected for the formation of adeno-associated virus (AAV) capsids based on different viral serotypes. Recen...